Co-benefits of integrating climate change adaptation and mitigation in the Canadian energy sector. (December 2017) - Hennessey, Ryan; Pittman, Jeremy; Morand, Annette; Douglas, Allan
Abstract: The integration of climate change adaptation and mitigation theoretically provides four co-benefits of interest to the Canadian energy sector: 1) reduced competition for resources, referring to capital savings resulting from improved project efficiencies; 2) reduced influence of scientific uncertainty for adaptations resulting from the shorter timelines and measurable outcomes of mitigation projects; 3) harmonization of implementation objectives resulting from synergies between mitigation and adaptation projects; and 4) improved social license of mitigation projects provided by accrual of local benefits derived from adaptation. Through the investigation of eleven case studies, our research demonstrates the presence of these co-benefits where integration is observed. Qualitative Comparative Analysis (QCA) is used to link observed input variables to identified co-benefits. This research suggests that integration is an effective means of generating co-benefits that contribute positively to project outcomes. The research further concludes that effective leadership support, either through public-private partnership and energy policy, is one means of achieving such explicit integration. Energy policy, in the form of voluntary instruments and incentives, is recommended to build necessary public-private partnerships and support leadership. Such policy recommendations have applications far beyond the energy sector and the lessons learned here can likely be applied to cases outside of it. Highlights: Four co-benefits of integration were identified in a literature review and demonstrated in a case study context. Based on eleven case studies these co-benefits are valued by the Canadian Energy Sector. Integration is occurring in a weak policy environment that supports it. Integration occurs through a combination of intent and leadership. Benefits are accruing through integration but accrual can be improved.